Fischer-Tropsch synthesis over lignin-derived cobalt-containing porous carbon fiber catalysts - Valero-Romero, María José; García-Mateos, Francisco José; Kapteijn, Freek; Rodríguez-Mirasol, José; Cordero-Alcántara, Tomás (Elsevier, 2023)
Cobalt-containing lignin-based fibers were synthesized in one step by electrospinning of Alcell lignin solutions as carbon precursor, a low-cost and renewable co-product of the paper making industry. The lignin fibers were thermostabilized in air to avoid the fusion during the carbonization process between 500 and 800 °C to obtain cobalt-containing porous carbon submicron fibers. These carbon fibers catalysts were studied for the Low-Temperature Fischer-Tropsch synthesis. The lignin-derived fibers containing Co catalyst located on the overall carbon fiber surface (internal and external) heat-treated at 500 °C (Co@CF-500) showed the best catalytic performance after 70 h on stream, with 75% and 60% selectivity to C5+ at 220 °C and H2/CO ratios of 1 and 2, respectively, attributed to the high Co dispersion, optimal Co-particle size and better Co accessibility. Higher heat-treatment temperatures leaded to Co-containing carbon fibers with larger metallic cobalt nanoparticles encapsulated in graphitic-type carbon, which rendered them inaccessible for FTS.
Keywords: Proceso Fischer-Tropsch; Fischer-Tropsch synthesis; Lignin; Electrospinning; Co-containing carbon fibers